Analysis Competition Coffee Exports From Producing Countries in the United States Market with Use Almost Ideal Demand System (AIDS) Model - Nasution, Suhela Putri; Wibowo, Rulianda Purnomo; Supriana, Tavi; ., Iskandarini (Journal of Ecohumanism, 2024)
For the Indonesian economy, coffee is one of the commodities plantation methods. Coffee's contribution to state revenues, especially in the form of foreign exchange, is what gives it its strategic worth. Indonesia follows Brazil, Vietnam, and Colombia as the world's top four coffee producers. Other nations besides Indonesia sell coffee to the US market, including Brazil, Vietnam, and Colombia. This study uses the Almost Ideal Demand System (AIDS) Model to examine competitiveness between coffee-supplying nations in the US market. Examine Data spanning 2003 to 2022 is used for this. According to research, Brazilian and Indonesian coffee prices are inelastic, whereas Vietnamese and Colombian coffee prices are elastic. Colombian, Vietnamese, and Indonesian coffee are competitors of Indonesian coffee. This is demonstrated by the mark elasticity positive cross (substitution), and Brazilian coffee has a complementary relationship.